Diversification of an emerging pathogen in a biodiversity hotspot: Leptospira in endemic small mammals of Madagascar. Issue 11 (17th May 2014) - Dietrich, Muriel; Wilkinson, David A.; Soarimalala, Voahangy; Goodman, Steven M.; Dellagi, Koussay; Tortosa, Pablo
Abstract Biodiversity hotspots and associated endemism are ideal systems for the study of parasite diversity within host communities. Here, we investigated the ecological and evolutionary forces acting on the diversification of an emerging bacterial pathogen, Leptospira spp., in communities of endemic Malagasy small mammals. We determined the infection rate with pathogenic Leptospira in 20 species of sympatric rodents (subfamily Nesomyinae) and tenrecids (family Tenrecidae) at two eastern humid forest localities. A multilocus genotyping analysis allowed the characterization of bacterial diversity within small mammals and gave insights into their genetic relationships with Leptospira infecting endemic Malagasy bats (family Miniopteridae and Vespertilionidae). We report for the first time the presence of pathogenic Leptospira in Malagasy endemic small mammals, with an overall prevalence of 13%. In addition, these hosts harbour species of Leptospira (L. kirschneri, L. borgpetersenii and L. borgpetersenii group B) which are different from those reported in introduced rats (L. interrogans) on Madagascar. The diversification of Leptospira on Madagascar can be traced millions of years into evolutionary history, resulting in the divergence of endemic lineages and strong host specificity. These observations are discussed in relation to the relative roles of endemic vs. introduced mammal species in the evolution and epidemiology of Leptospira on Madagascar, specifically how biodiversity and biogeographical processes can shape community ecology of an emerging pathogen and lead to its diversification within native animal communities.